Quotes from the Quaid - Jinnah, Muhammad Ali; Edited by Sharif-Al-Mujahid; Liaquat Merchant; Foreword by Wolpert Stanley (Karachi Oxford University Press, 2007)
This handy booklet offers a compilation of quotations culled from the life's work of the founder of Pakistan, Mohammad Ali Jinnah. These inspiring quotes are eminently purposive spelling out Jinnah's vision of Pakistan in his own words. This is a book that should be read by every Pakistani, and by all others who seek to understand the vision behind Pakistan. Although Jinnah spoke on a multitude of issues in the course of his long and illustrious career, this compilation includes his words and thoughts on areas relevant to contemporary Pakistan and provides guidance to Pakistanis in various essential areas of public and private life.
Include Illustration and Chronology.
Keywords: Jinnah, Mahomed Ali, 1876-1948 -- Pakistan -- Politics and government